Assessing the comprehension and numerical skills in physics: Challenges encountered by non-stem students in solving worded – problems - Midtimbang, Asraf A.; Unsi, Alibai L.; Bakal, Bai Dinah S.; Camua, Amour M.; Dante, Rohaina P.; Untong, Leonela Bai P.; Mamucao, Princess Sheryn A. (Edelweiss Applied Science and Technology, 2026)
This descriptive study investigated the comprehension levels, numerical skills, learning behaviors, and difficulties of non-STEM senior high school students in solving physics word problems. The respondents were 100 non-STEM students from Dimaukom National High School who completed tests and survey questionnaires. Reading comprehension was assessed using the Philippine Informal Reading Inventory (PIRI) of the Department of Education, while numerical skills were measured through an adapted DepEd Numeracy Assessment Tool. Students’ difficulties in physics problem-solving were identified using a test focusing on unit conversion, formula selection, and mathematical operations. Learning behaviors, attitudes, and interests toward physics were examined using Wrenn’s Study Habit Inventory, Entwistle’s Student Attitude Inventory, and the Guilford-Zimmerman Interest Inventory. Results showed that students were at the instructional level in reading comprehension and moderately numerate, suggesting the need for academic intervention. Survey findings indicated that students generally found physics unengaging, as reflected in their poor study habits, attitudes, and interest. Among the identified challenges, mathematical operations were the most difficult, followed by selecting appropriate formulas and converting units. Overall, non-STEM students were more comfortable with simple calculations than with complex, multi-step worded physics problems.